The Detection of Genital Actinomyces by Cytological and Microbiological Methods - Dilek Kaya; Şayeste Demirezen; Gülşen Hasçelik; Serpil Erciş; Mehmet Sinan Beksaç (Medical Network, 2009)
OBJECTIVE: To detect the genital Actinomyces in women by both cytological and microbiological methods. STUDY DESIGN: Cervico-vaginal samples were obtained from 200 patients attending the Gynecology and Obstetrics Clinics of Hacettepe University. All these samples were screened in view of Actinomyceslike organisms (ALOs) cytologically and were examined microbiologically by the BBL Crystal Identification System with regard to the presence of Actinomyces. RESULTS: ALOs was detected in 6 (3%) women by cytological method and Actinomyces positivity was found in 7 (3.5%) samples by the BBL Crystal ID System. Of 6 samples that gave positive results by Pap-staining, only one was positive by the BBL Crystal ID system. We found a lack of agreement statistically between these methods (p>0.05) for the detection of Actinomyces. CONCLUSION: The detection of genital Actinomyces both in smears and cultures might be more sensitive to prevent the misdiagnosed and undiagnosed cases and for early diagnosis and treatment.